2014
DOI: 10.12691/ajams-2-1-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Automated Teller Machine on the Performance of Nigerian Banks

Abstract: This study investigates the effects of ATM on the performance of Nigerian banks. Available studies have concentrated on the significant dimensions of ATM (automated teller machine) service quality and its effect on customer satisfaction with a bias against ATM producers. The study is motivated by the astronomical challenges confronting the proliferation of ATM infrastructure and attendant financial losss to banks which are often underreported. Also, there are serious debate on the relevance of ATM technology a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 7 publications
1
12
0
Order By: Relevance
“…Therefore, it was concluded that ATM usage is highly related to operational performance. This study is consistent with the findings of [6] who argued that Automated Teller Machines contribute to the effectiveness of banking sector. He further argued that Automated Teller Machine stimulate banking industry growth.…”
Section: Relationship Between Automated Teller Machines Usage and Opesupporting
confidence: 93%
See 1 more Smart Citation
“…Therefore, it was concluded that ATM usage is highly related to operational performance. This study is consistent with the findings of [6] who argued that Automated Teller Machines contribute to the effectiveness of banking sector. He further argued that Automated Teller Machine stimulate banking industry growth.…”
Section: Relationship Between Automated Teller Machines Usage and Opesupporting
confidence: 93%
“…Reasons for the introduction of ATMs in retail banking include lower labour cost, efficiency, greater consumer involvement, standardization of service delivery, customer satisfaction and loyalty. [6] contends that less than the benefits, the deployment of ATMs terminals have averagely improved the performance of Nigerian banks because of the alarming rate of ATM fraud. According to [10], convenience, reliability, ease of use, privacy, security, responsiveness and fulfillment were found to be the major dimensions of ATMs service quality.…”
Section: Automated Teller Machines (Atms)mentioning
confidence: 99%
“…This study produced results which corroborate the findings of a great deal of the previous work in this field. A number of relevant studies tied the expansion of ATM networks with the improvement in the banks' profitability (Humphrey, 1994;Jegede, 2014;Akhisar et. al., 2015;Shihadeh et.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the study concluded that the users of the banks' services have benefited more from using ATMs than the banks have. Similarly, (Jegede, 2014) has concluded that the expansion in using ATMs will improve the performance of Nigerian banks, contribute to the effectiveness of the banking sector, and enhance the opportunities of bank growth.…”
Section: Literature Review Of the Relationship Between Financial Inclmentioning
confidence: 99%
“…Thus, the current study seeks to investigate if the total number of customers has an impact on profitability, as well as private and legal customers, could be considered separately as influencing factors. Authors researching bank profitability issues claim that number of automated teller machines (ATMs) could improve profitability (Akhisar et al, 2015;Jegede, 2014;Le & Ngo, 2020;Ramila & Gurusamy, 2016;Salimi et al, 2013;Turkoglu & Genevois, 2017). In line with ATMs, the number of payment cards could play a vital role in maximising bank's profitability, as they are used to reach customers via a point of sale (POS) and ATMs; hence, the number of payment cards is considered to be another independent variable (Hamdi et al, 2017;Le & Ngo, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%